The adoption of Korean popular culture among IIUM students - Ali, Habib; Wok, Saodah; A. Manaf, Aina Maznina; Jamalludin, Nur Hafifah (Kolej Universiti Islam Melaka, 2019)
The presence of Korean wave in Malaysia has led Malaysians to focus more on Korean society and its culture. The purpose of this study is to find out the adoption of Korean popular culture by students in International Islamic University Malaysia (IIUM). Specifically, this study examines the relationship between media exposure, perception, attitude and adoption of Korean popular culture. Perception and attitude are the mediators to the relationship between media exposure and adoption of Korean popular culture. The underpinning theory for this study is cultivation theory. This study employs a quantitative research design using the survey method. Both online and self-administered questionnaires were used for data collection. A total of 420 respondents participated in the survey. Findings showed that the respondents are exposed to Korean popular culture mainly through television and radio. They have a positive perception and attitude towards Korean popular culture and they are also positively adopting the Korean popular culture. There is a positive relationship between media exposure, perception, attitude and adoption of Korean popular culture. Perception and attitude partially mediate the relationship between media exposure and the adoption of Korean popular culture. Cultivation theory is partially supported by this research.